(untitled) (JOISCO: Journal of Islamic Communication, 2024)
This paper aims to reveal the strategy of The Center for Quality Assurance (LPM) UIN Alauddin in disseminating STILeS-based subject learning modules. It is a descriptive qualitative method using communication management approach. Data collected through observation, interview, and documentation. Instruments used in this research were observation note, list of interview query, camera, HP and MP4. In analyzing data the researcher used Miles and Hubermen’s method namely data reduction, data display, conclusion drawing and verification. The results showed that in socializing the STILeS, LPM implemented 4 strategies. 1. Conducted training, which consists of two stages, namely the orientation of STILeS design and mentoring its application. 2. Using social media, through address website http://cequence.uin-alauddin.ac.id/Held a scientific seminar. 3. Published STILeS that can be a learning guideline for Lecturers and Students. The challenges faced by LPM in disseminating STILeS: First, in the level of awareness, there are still lecturers who have not applied the learning system. Second, the supporting facilities for learning system still need to be equipped. Third, copying modules especially those held by students, because students must have modules for each programmed course.